Gastric neuroendocrine tumor associated with rapidly progressive glomerulonephritis - Viteri Cevallos, Diego (2015)
Introduction: Gastric neuroendocrine tumors are rare lesions derived from enterochromaffin cells, whose presentation depends on its pathogenesis and biological and histopathological characteristics, with a wide variety of clinical presentation, which deserves an integral vision for a diagnosis and timely managment. Case Report: This is the case of a 33 years old woman who enters to the Nephrology Service diagnosed with rapidly progressive glomerulonephritis, during her clinical evaluation and complementary studies, a neuroendocrine tumor was found at the gastric level the patient received surgical management and a clinical improvement is achieved as well as the laboratory with favorable outcome. Conclusions: A paraneoplasic syndrome is presented, secondary to a neuroendocrine gastric tumor, the medical reports are very rare in the literature, since the patient presented data from a rapidly progressive glomerulonephritis. She required a multidisciplinary management in which was possible to correct the cause of her suffering, but long term with the risk of chronic renal damage.